Determination of the Solvent Blue 35 dye in diesel fuel by solid phase extraction and high-performance liquid chromatography with ultraviolet detection. (March 2018) - Tomić, Tatjana; Babić, Sandra; Biošić, Martina; Nasipak, Nada Uzorinac; Čižmek, Ana-Marija
Abstract: The method for the determination of blue dye Solvent Blue 35 (SB 35) in diesel fuel by high performance liquid chromatography (HPLC) coupled with UV-VIS detection was developed. The dye is separated from the hydrocarbon sample matrix and determined as a single component at 650 nm wavelength. Solid phase extraction (SPE) on the silica based solid phase sorbent was used as a pre-treatment method. Among investigated elution solvent mixtures, the mixture composed of chloroform and heptane in the volume ration of 1:0.75 ( v / v ) provided the best SB 35 recovery. During method validation two calibration models were tested: external calibration and matrix-matched calibration. For both models correlation coefficients were higher than 0.99 and slopes were compared using the Student's t -test. Precision was evaluated as repeatability and intermediate precision with relative standard deviations less than 7%. Low limit of quantification of 0.1 mg L −1 were obtained. Optimized procedure using 250 mg of sorbens provided recoveries ranged from 76.9% to 99.4% over a linear range (0.1–10 mg L −1 ). The developed method has been applied to the analysis of blue diesel samples from the market and suspicious samples. The content of SB 35 dye in a commercial blue diesel samples was found to be around 0.5 mg L −1 while presence of SB 35 dye in suspicious sample was confirmed. Highlights: The method for determination of blue dye SB 35 in diesel fuel was developed. Sample pretreatment was performed by optimized SPE. Satisfactory extraction recovery was obtained. Low limits of detection, good precision and accuracy were achieved. Determination of SB 35 dye in suspicious diesel fuel sample was accomplished.